Extraction of Ln(III) and An(III) by N, N-di(2-ethylhexyl)- thio-diglycolamic Acid. Issue 6 (19th September 2022) - Jin, Chang; Liu, Qian; Du, Yu; Xu, Chao; Liu, Tingting; Fang, Tuo; Wang, Ganlin; Zhu, Liyang; Zhang, Yan; Yang, Suliang; Tian, Guoxin
ABSTRACT: The extraction of Nd(III), Eu(III), Am(III), and Cm(III), trivalent lanthanides and actinides in high level nuclear waste, by the extractant N, N -di(2-ethylhexyl)-thio-diglycolamic acid (HDEHSDGA, HA) is investigated via thermochemical and spectroscopic methods. In this study, HDEHSDGA behaves as a conventional mono-basic cation-exchanging ligand extracting Ln(III) and An(III) from nitrate solutions of pH region. The information obtained from the extraction experiments and the spectroscopic analyses indicate that the primary extracted complex species may be MA3  · 2H2 O for these four cations and likely for the other trivalent f-elements. In the extracted complexes, the anionic monomer extractant A − coordinates to the metal ions presumably forming bidentate coordination via the carbonyl oxygen atom and one of the oxygen atoms of the carboxylate; it appears that the thio-ether does not directly participate in the complexation reaction. The results ultimately demonstrate that HDEHSDGA does not exhibit significant selectivity for An(III) over Ln(III), in contrast to results reported in a previous study conducted with unpurified extractant.